2012
DOI: 10.1088/0953-8984/24/12/125401
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigations on an amorphous Se90Te10alloy produced by mechanical alloying using EXAFS, cumulant expansion and RMC simulations

Abstract: We investigated an amorphous Se(90)Te(10) alloy produced by mechanical alloying using two different approaches. First, we used extended x-ray absorption fine structure (EXAFS) spectroscopy and the cumulant expansion method using the Einstein model for the temperature dependence of the cumulants to obtain the cumulants C(*)(1), C(*)(2), and C(*)(3). From these, we found information about the structure of the alloy as well as the thermal and structural disorder, anharmonicity of the effective interatomic pair po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…An evident problem in the analysis of the EXAFS data coming from 0D systems concerns in the fact that the Debye-Waller factors,  j 2 in eqn , (5), have a double thermal and static nature [817][818][819]. The former follows the standard temperature trend foreseen by the Einstein model [820][821][822][823][824][825][826], the latter is due to a spread in average interatomic distances undergone by the atoms at the surface of the NPs.…”
Section: Xas Characterization Of Zero Dimensional Structures: a Brief...mentioning
confidence: 99%
“…An evident problem in the analysis of the EXAFS data coming from 0D systems concerns in the fact that the Debye-Waller factors,  j 2 in eqn , (5), have a double thermal and static nature [817][818][819]. The former follows the standard temperature trend foreseen by the Einstein model [820][821][822][823][824][825][826], the latter is due to a spread in average interatomic distances undergone by the atoms at the surface of the NPs.…”
Section: Xas Characterization Of Zero Dimensional Structures: a Brief...mentioning
confidence: 99%
“…The algorithm of the standard RMC method is described elsewhere 56,57 and its application to different materials is reported in the literature. 48,[66][67][68][69][70] The idea is to minimize the function…”
Section: B Rmc Simulationsmentioning
confidence: 99%
“…This result is different from those found for other Se-based alloys, where the heteropolar pair is stronger than the Se-Se pair. For comparison, Kostrzepa et al 70 obtained k E e,Se-Se = 9.2 eV/Å 2 and k E e,Se-Te = 18.2 eV/Å 2 , for a-Se 90 Te 10 , Machado et al 74 found k E e,Se-Se = 10.6 eV/Å 2 and k E e,Se-P = 13 eV/Å 2 , for a-Se 90 P 10 , and, for a-InSe 9 , Machado et al 75 obtained k E e,Se-Se = 7.6 eV/Å 2 and k E e,Se-In = 8.6 eV/Å 2 . The average interatomic distances, that correspond to the first cumulant C 1 , can be seen at Fig.…”
Section: A Exafs Analysismentioning
confidence: 99%